Evaluating the effects of polices on nursing care as promoted by the Veneto region: the research protocol and its implications for public health - Di Falco, A.; Costa, C.; Bottega, M.; Fanton, E.; Zambon, A.; Brugnaro, L.; Stevanin, S.; Roncoroni, E.; Allegrini, E.; Degan, M.; Capirossi, G.; Bonesso, P.; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The Veneto region has recently defined a set of policies on nursing care by determining the needed amount of daily care in minutes and by initiating a systematic measurement of nursing outcomes; also, with a more recent policy, missed nursing care (MNC) has been established as a process measure of interest. To measure the effect of these policies, a research protocol - aimed at evaluating several end points - has been designed, involving a large target population and hospital units. The aim of this manuscript is to briefly present the research protocol and to discuss the public health implications of its expected end-points. Study design. Multi-centre mixed-method study design organised into several phases. Methods. The endpoints of the protocol are: (a) to describe the frequency of MNC as perceived by nurses; (b) to identify contributing factors; (c) to identify practices adopted in low-occurrence MNC units and to assess the effectiveness of implementing them in units with higher levels of MNC; (d) to explore the relationship between the amount of nursing care provided, MNC, and patient outcomes; and (e) to validate a tool that measures MNC as perceived by patients/caregivers. A total of 3,460 nurses, 5,000 patient/day and 160 nursing coordinators of the medical and surgical units of public hospitals in the Veneto Region will be included. Conclusions. Measuring the association between the amount of nursing care and patient outcomes, as well as evaluating the role of MNC as perceived by nurses and patients in hindering or increasing the risk of some patient outcomes can provide a body of evidence capable of further informing policies in the field, both at the national and at the international level. Moreover, emerging good practices capable of preventing or minimising MNC, sharing and implementing them in other units where high levels of missed care are reported and evaluating their effectiveness, can also inform public health policies.